The first preserved nasal cavity in the human fossil record: The Neanderthal from Altamura - Costantino Buzi; Antonio Profico; Carlos Lorenzo; Giorgio Manzi (Proceedings of the National Academy of Sciences, 2025)
The nose of Neanderthals and its possible adaptation to harsh climatic conditions is a longstanding matter of debate in paleoanthropology. Here, we present and describe the complete inner nasal structures of the early Neanderthal skeleton from Altamura, southern Italy. It represents evidence hitherto unavailable, both for this species and the human fossil record in general, and sheds light on the possible influence of respiratory adaptations on the characteristic Neanderthal facial morphology. Part of the debate has revolved around inner nasal traits proposed as unique adaptations (autapomorphies) of the species Homo neanderthalensis in relation to cold climate, specifically: a vertically oriented medial projection and a medial swelling on the nasal cavity wall alongside the lack of an ossified roof over the lacrimal groove. The lack of complete anatomy in the Neanderthal fossil record further livened the discussion regarding their occurrence. With the description and analysis of this unique finding, we can rule out the existence of such features. In addition, our observations corroborate the hypothesis that the characteristic midfacial morphology of H. neanderthalensis (i.e., the midfacial prognathism) is the result of a combination of factors and not a direct result of respiratory adaptations in the upper airways. Finally, our data provide an enhanced perspective for modeling Neanderthal respiratory performances.